THEORETICAL APPROACH ON TARGETING PLANT FUNGAL PATHOGENIC PROTEINS AGAINST NATURALLY ISOLATED COMPOUNDS FROM CHITINIPHILUS SHINANONENSIS - S, KRITHIKA; C, CHELLARAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to find the potency and bioefficacy of Asiatic acid and triterpene against four different plant fungal pathogens using a structure-based drug designing approach. Methods: The pathogenic fungus which causes a dreadful effect on plants is reviewed from literature study, and its three-dimensional structures are retrieved from the protein data bank database. On the other hand, ligands are prepared. Finally, prepared fungal drug targets are docked with naturally isolated compounds using AutoDock tools. Results: Both compounds Asiatic acid and triterpene structures are complementary to bind at the active site of four different drug targets. Comparatively, it is more favorable for Avr2 effector protein from Fusarium oxysporum with Ki value of 126.60 μM, 1.76 μM, and dock score value of −5.32 kcal/mol and −7.85 kcal/mol for Asiatic acid and triterpene, respectively. Thus, interaction analysis was carried out only for these protein-ligand complexes. Conclusion: The computational biology study states that these two compounds can be the lead candidate for treating disease caused by plant fungal pathogen F. oxysporum. However, further study has to be done in vitro and in vivo to prove its same efficacy.